2015
DOI: 10.17116/oftalma2015131219-25
|View full text |Cite
|
Sign up to set email alerts
|

Ocular blood flow and carotid artery malfunction

Abstract: OBF-based estimation of individual normal range of IOP is inexpedient in patients with greater than 80% carotid artery stenosis due to its possible influence on ocular hemodynamics. In most cases of less than 80% carotid artery stenosis OBF is adequate or slightly reduced as compared to its AL-dependent norm and thus, has no significant impact on estimated individual normal range of IOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
1
0
1
Order By: Relevance
“…High CIMT values may possibly reflect reduced blood flow in choroidal blood vessels that may have an effect on retinal/choroidal function resulting in choroidal thinning and decreasing of ganglion cell thickness. In another study including patients with different degrees of internal carotid artery stenosis, OCT showed thinning of retinal ganglion cell and nerve fiber layers [16]. In the present study, OCT scans revealed slight thinning of the GCIPL thickness.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…High CIMT values may possibly reflect reduced blood flow in choroidal blood vessels that may have an effect on retinal/choroidal function resulting in choroidal thinning and decreasing of ganglion cell thickness. In another study including patients with different degrees of internal carotid artery stenosis, OCT showed thinning of retinal ganglion cell and nerve fiber layers [16]. In the present study, OCT scans revealed slight thinning of the GCIPL thickness.…”
Section: Discussionsupporting
confidence: 63%
“…Although the relationship seems to be weak CIMT was inversely associated with choroidal thickness in all peripapillary and parafoveal areas. There have been several reports investigating the relationship between ocular structures and carotid vessels [13][14][15][16][17]. Agladioglu et al [13], found that choroidal thickness was negatively correlated with ICA diameter and ICA resistance index in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…В структуре заболеваний ЗН лидирующие позиции занимают оптический неврит (30-40 % случаев) и ишемическая оптическая нейропатия (59 % случаев). До внедрения в офтальмологическую практику ОКТ эхография оставалась единственным объективным методом диагностики папиллита и ретробульбарного неврита (РБН) [27][28][29]. Комплексное исследование ЗН с использованием ОКТ и УЗИ у пациентов с папиллитом показало одно-или двустороннюю проминенцию ДЗН более чем на 1 мм и утолщение орбитальной части ЗН с расширением периневрального пространства при РБН [29].…”
unclassified